Human Rights Challenges and Their Implications from the Perspective of Islamic Law and Education - Ahmas Naqieb Faaz; Tasman Hamami (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2025)
Despite the recognition of equality as a fundamental human right in both the Universal Declaration of Human Rights and Indonesian law, its implementation is often obstructed by various human rights violations. Many human rights cases remain unresolved, thus becoming a historical burden. This study investigates human rights issues from the perspectives of Islamic law and education, drawing on the principles of Maqashid as-Shari'ah and a theo-anthropocentric framework. The research aims to identify the gap between the ideal human rights norms and their actual application in society. A qualitative approach, using a prescriptive method, is employed to analyze normative principles and their practical implications through text analysis and literature review. The findings suggest that, while human rights are inherent to every individual, with the principle of equality before the law, their implementation encounters significant structural and cultural obstacles. The study also highlights the vital role of Islamic education in cultivating awareness and respect for human rights from an early age. This research contributes to bridging the divide between Islamic law and global human rights frameworks, advocating for the integration of ethical and humanistic principles into the Islamic legal and educational systems to address human rights challenges. By promoting democratic values and respect for human rights, Islamic education plays a critical role in fostering a more just and equitable society.